Muscle phenotype in patients with myotonic dystrophy type 11. Issue 3 (21st November 2012) - Andersen, Grete; Ørngreen, Mette C.; Preisler, Nicolai; Colding‐J⊘rgensen, Eskild; Clausen, Torben; Duno, Morten; Jeppesen, Tina D.; Vissing, John
<x xml:space="preserve">Abstract</x> Introduction: The pathogenesis of muscle involvement in patients with myotonic dystrophy type 1 (DM1) is not well understood. In this study, we characterized the muscle phenotype in patients with confirmed DM1. Methods: In 38 patients, muscle strength was tested by hand‐held dynamometry. Myotonia was evaluated by a handgrip test and by analyzing the decrement of the compound muscle action potential. Muscle biopsies were assessed for morphological changes and Na+‐K+ pump content. Results: Muscle strength correlated with a decline in Na+‐K+ pump content (r = 0.60, P < 0.001) and with CTG expansion. CTG expansion did not correlate with severity of myotonia, proximal histopathological changes, or Na+‐K+ pump content. Histopathologically, we found few centrally placed nuclei (range 0.2–6.9%). Conclusions: The main findings of this study are that muscle weakness correlated inversely with CTG expansion and that central nuclei are not a prominent feature of proximal muscles in DM1. Muscle Nerve 47:409‐415, 2013